Pengaruh Debt to Equity Ratio dan Sales Growth terhadap Net Profit Margin pada Perusahaan Ritel Terdaftar di ISSI Periode 2021-2025 - Reihan Fajri Ihsan; Gina Havieza Elmizan (ARZUSIN, 2026)
Profitability is an important indicator for assessing a company’s financial performance and sustainability; however, studies examining the effects of the Debt to Equity Ratio (DER) and Sales Growth on the Net Profit Margin (NPM) of retail-sector companies listed on the Indonesia Sharia Stock Index (ISSI) during the 2021–2025 period remain limited. This study aimed to analyze the effects of DER and Sales Growth, both partially and simultaneously, on NPM. The study employed a quantitative approach with a causal design. The study population comprised retail-sector companies listed on the ISSI during the 2021–2025 period, while the sample consisted of 11 companies with 55 observations selected through purposive sampling. Secondary data were obtained from the companies’ annual financial statements and analyzed using panel data regression with the Fixed Effect Model (FEM) through EViews 13 software. The results showed that DER had a negative and significant effect on NPM, whereas Sales Growth had a positive and significant effect on NPM. Simultaneously, DER and Sales Growth had a significant effect on NPM. These findings provide empirical evidence for the development of Trade-Off Theory and the Theory of the Growth of the Firm in explaining the relationships among capital structure, sales growth, and corporate profitability. This study emphasizes that increasing the profitability of retail-sector companies requires prudent capital structure management and the optimization of sales growth. In practical terms, the results can serve as a consideration for management in formulating financing policies and sales strategies that support improved financial performance. Future research should consider other financial variables and expand the scope of companies and observation periods to obtain more comprehensive findings.